Korektor Postur Duduk untuk Remaja: Analisis Fungsional - Sumarsono Putri, Hyacintha; Hairunnas; Hartono, Markus (CandraRupa : Journal of Art, Design, and Media, 2025)
The habit of sitting hunched over in adolescents is one of the risk factors for postural disorders that can have an impact until adulthood. Sitting posture correctors are present to aid in forming ideal sitting habits. This study aims to analyze the specifications of existing sitting posture corrector products and the needs and preferences of adolescents regarding the use of sitting posture correctors. The results of the analysis show that existing sitting posture correctors have adjustable features so that they can be adjusted to environmental conditions. In addition, adolescents are enthusiastic about the existence of sitting posture corrector products, especially those that have a practical design, are comfortable to use, and are easy to operate. Sitting posture correctors that are commonly preferred by adolescents have a curved cushion shape, with a fairly soft or at least smooth texture, and a long adjustment range. By considering the variations in adolescent physical conditions and user preferences, the development of an adjustable and dismantled sitting posture corrector is considered functional for use in forming better sitting posture habits in adolescents.